HUBUNGAN KUALITAS SDM, KOMPETENSI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT. FEVA INDONESIA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - M Risqi Pratama; Randika Fandiyanto; Riska Ayu Pramesthi (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Human resources (HR) are a vital component within a company. Factors that influence HR include competence, career development, and work motivation. This study aims to examine and analyze both the direct effects of human resource quality, competence, and career development on employee performance, as well as their indirect effects through work motivation. The research was conducted at PT. Feva Indonesia conducted a study with a sample of 36 field employees selected using total sampling, where the entire population was used as the sample. The unit of analysis is PT. Feva Indonesia, focusing on employees in operational roles as respondents. Data analysis and hypothesis testing were carried out using the Partial Least Squares (PLS) approach with SmartPLS 3.0 software. The results indicate that human resource quality has a significant positive effect on motivation. Competence has a positive but insignificant effect on motivation. Career development has a significant positive effect on motivation. Human resource quality has a positive but insignificant effect on performance. Competence has a significant positive effect on performance. Career development has a significant positive effect on performance. Motivation has a positive but insignificant effect on performance. Additionally, human resource quality, competence, and career development each have a positive but insignificant indirect effect on performance through motivation.